2019
DOI: 10.1039/c8fo02448k
|View full text |Cite
|
Sign up to set email alerts
|

A curcumin derivative, WZ35, suppresses hepatocellular cancer cell growthviadownregulating YAP-mediated autophagy

Abstract: HCC is a common cancer type in the world. Here, we found WZ35, a novel derivative of curcumin, could notably suppress HCC cell growthviainhibiting YAP controlled autophagy, highlighting the potent anti-tumor activity of WZ35 in liver cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Similarly, numerous previous in vitro and in vivo studies have demonstrated that curcumin inhibits the growth cancer in both animals and humans (40-42), including hepatocellular carcinoma (43). Several reports have suggested that curcumin or its derivative alone or in combination with other drugs exhibit favorable anti-liver cancer activity (44)(45)(46). Shao et al (47) reported that bisdemethoxycurcumin, a natural dimethoxy derivative of curcumin, decreases the number of tumor-infiltrating MDSCs in MB49 metastasized bladder cancer cells.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, numerous previous in vitro and in vivo studies have demonstrated that curcumin inhibits the growth cancer in both animals and humans (40-42), including hepatocellular carcinoma (43). Several reports have suggested that curcumin or its derivative alone or in combination with other drugs exhibit favorable anti-liver cancer activity (44)(45)(46). Shao et al (47) reported that bisdemethoxycurcumin, a natural dimethoxy derivative of curcumin, decreases the number of tumor-infiltrating MDSCs in MB49 metastasized bladder cancer cells.…”
Section: Discussionmentioning
confidence: 91%
“…When administered to BALB/c nude mice bearing HCCLM3 cells, WZ35 (20 mg/kg, i.p.) suppressed tumor growth more efficiently than curcumin and large areas of necrosis were present in treated tumors [237].…”
Section: Curcuminoidsmentioning
confidence: 95%
“…Numerous papers have examined the natural phytopolyphenol, curcumin, in terms of its antitumorigenesis and therapeutic properties [471]. Administration of curcumin to Huh7 cells precipitated early autophagy, as evidenced by autophagic vacuolar evolution [472].…”
Section: Targeting Autophagymentioning
confidence: 99%